DISTRIBUTION OF INHERITANCE BASED ON THE PRINCIPLE OF JUSTICE ACCORDING TO NATIONAL LAW - Eleanora, Fransiska Novita; Sari, Andang (Fakultas Hukum Universitas Muhammadiyah Magelang, 2019)
Inheritance is an object that has been given by an heir in the form of a moving or immovable object. Distribution of inheritance often causes inheritance disputes between parties who receive an inheritance. The assets and inheritance that are disputed sometimes give harm to parties outside the heirs. The system and rules governing inheritance are very necessary for a country known for its diverse customs, one of which is Indonesia. This study aims to investigate the principle of justice in distributing inheritance based on the compilation of Islamic law (KHI). The method used in this study is library research using various literature and legislation. The results of the study show that the distribution of inheritance among the parties has not referred to the national legal system but is still based on a legal system agreed upon by the parties. They have the right and can use and choose which law to use for their inheritance. Existing laws will always provide and accommodate various forms of taste and justice created in the lives of the general public and in that case, are the same age as an inheritance under various systems and laws and that are truly trusted by the heirs.